Pure Cortical Ependymoma With RELA-Fusion Positive in a Young Adult - Lee, Sang-Woo; Lee, Jeong-Ho; Lee, Min-Seok; Suh, Sang-Jun; Lee, Yoon-Soo; Kim, Jin-Wook (Brain tumor research and treatment, 2021)
A 25-year-old female presented with a generalized tonic-clonic seizure. She had no previous history of seizures. A brain magnetic resonance imaging scan revealed a solitary enhancing mass in the right fronto-parietal cortex. During surgery, the mass was noted to be pure cortical with no connection to the ventricular lining. The tumor was completely resected. After surgery, the patient had no further seizures. The biopsy result showed a supratentorial ependymoma, which was C11orf95-RELA-fusionpositive.A 25-year-old female presented with a generalized tonic-clonic seizure. She had no previous history of seizures. A brain magnetic resonance imaging scan revealed a solitary enhancing mass in the right fronto-parietal cortex. During surgery, the mass was noted to be pure cortical with no connection to the ventricular lining. The tumor was completely resected. After surgery, the patient had no further seizures. The biopsy result showed a supratentorial ependymoma, which was C11orf95-RELA-fusionpositive.